Creation of a Cleft in an Angiography Catheter to Facilitate Catheterization of Branches of the Aorta Arising at an Acute Angle - Miyayama, Shiro; Yamashiro, Masashi; Okuda, Miho; Aburano, Hiroyuki; Shigenari, Noriaki; Morinaga, Kyoko; Matsui, Osamu (Journal of vascular and interventional radiology, 2008)
The authors report on the use of a catheter with a cleft for catheterization of a branch artery arising from the aorta with an acute angle. The cleft was created on either the right or cephalad portion at the tip of a seated 4-F shepherd hook catheter in the artery origin, depending on vessel angulation during chemoembolization procedures. This catheter was used in eight arteries—seven inferior phrenic arteries and one right subcostal artery—that could not be catheterized with a conventional coaxial technique. The microcatheter was successfully introduced into all eight vessels through the cleft without complications.